Biodegradation of lignin by Pseudomonas sp. Q18 and the characterization of a novel bacterial DyP-type peroxidase. (1st October 2018) - Yang, Chenxian; Yue, Fangfang; Cui, Yanlong; Xu, Yuanmei; Shan, Yuanyuan; Liu, Bianfang; Zhou, Yuan; Lü, Xin
Abstract: Lignin valorization can be obtained through cleavage of selected bonds by microbial enzymes, in which lignin is segregated from cellulose and hemicellulose and abundant phenolic compounds can be provided. In this study, Pseudomonas sp. Q18, previously isolated from rotten wood in China, was used to degrade alkali lignin and raw lignocellulosic material. Gel-permeation chromatography, field-emission scanning electron microscope, and GC–MS were combined to investigate the degradation process. The GC–MS results revealed that the quantities of aromatic compounds with phenol ring from lignin increased significantly after incubation with Pseudomonas sp. Q18, which indicated the degradation of lignin. According to the lignin-derived metabolite analysis, it was proposed that a DyP-type peroxidase (PmDyP) might exist in strain Q18. Thereafter, the gene of PmDyP was cloned and expressed, after which the recombinant PmDyP was purified and the enzymatic kinetics of PmDyP were assayed. According to results, PmDyP showed promising characteristics for lignocellulosic biodegradation in biorefinery.